Patients having surgery for ulnar nerve compression at the elbow rarely have affection of the spinal nerve root at C8-Th1 levels - Nyman, Erika; Giöstad, Alice; Abul-Kasim, Kasim; Dahlin, Lars B. (Frontiers in Surgery, 2022)
Cervical pathology may contribute to residual problems after surgery for ulnar nerve compression. We aimed to evaluate the presence of pathological conditions in spinal cord and cervical spinal nerve roots in patients surgically treated for ulnar nerve compression at elbow. In a cohort of patients, surgically treated for ulnar nerve compression at elbow, magnetic resonance images (MRI; performed 3 years pre/postoperatively) were evaluated by a neuroradiologist blinded to patient characteristics and outcome of surgery. Cervical conditions were assessed and related to patient characteristics, preoperative McGowan grade, and outcome. Among 62 patients (45 unilaterally and 17 bilaterally), only one had spinal nerve root affection of nerve roots contributing to the ulnar nerve (C8-Th1). About half of the patients, mainly those at higher age, had alterations affecting C3-C7 spinal nerve roots at both surgically and non-surgically treated sides. Only few other changes were observed at cervical levels. A high McGowan grading was related to a high frequency of spinal nerve root affection. Smokers were more frequently observed among those with spinal nerve root affection at C3-C7 levels at surgically treated side. Residual problems, expressed as patient dissatisfaction and DASH score ≥40, were common. Spinal nerve roots, contributing to the ulnar nerve, are rarely affected in surgically treated patients with ulnar nerve compression at elbow even though pathology is often observed at other cervical levels. Pathology is often detected at other cervical spinal nerve root levels at surgically and non-surgically treated sides, particularly among older patients, smokers, and in conjunction with worse preoperative McGowan grade. No relation between cervical pathology and outcome of ulnar nerve surgery is seen.